Risco e vitimização policial militar: da caserna à política - Joly, Bruno Renan (2017)
The present work aims to outline the issue of risk, victimization and the suffering of the military police as factors that more than inherent to the profession are reinforced by the manner the public security in Brazil is structured. We show that the victimization of the military police goes far beyond death, being constituted by issues related to mental illness, persecution, exclusion, suicide, class conflicts and gender. We also bring to the discussion the problematization of the precarious working conditions to which the praças – low-ranking police officers – of the military police are subjected to, and how this reinforces the high and complex victimization situation. Finally, we identify a scenario in which there is a dispute around the truth concerning the issues that afflict the praças: on the one hand, the associations of this military police workers that intend to represent in the legal and political sphere a whole class of professionals devoided of the right to this representation. On the other hand, the parliamentarians of the so-called "bancada da bala", which use elements such as the high death rates among the military police to support political positions of hardening and militarization of public security. In a context where this issue has become a political agenda and an open discussion between the police and civil society, attempts are made to understand how this movement occurs, given that the military police is a sealed institution and its internal directives hardly become public. We analyse the role of both the praças association and the parliamentarians of “bancada da bala” on this issue. Through bibliographic review, analysis of quantitative data and semi-structured interviews, we seek to explore how the issue of police suffering is subjectivated by these professionals and what are the implications for both professionals in their personal lives and public security. It is concluded that the military police agents live a regime of exception within a democratic regime and that, therefore, they end up becoming guarantors of a social order based on the duties and not the rights.